2022
DOI: 10.1002/pcn5.28
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the number of antipsychotics prescribed and metabolic parameters in Japanese patients with schizophrenia

Abstract: Aim: There is little evidence on the effects of antipsychotic polypharmacy on metabolic parameters in patients with schizophrenia. Thus, this cross-sectional study explored the associations between the number of antipsychotics prescribed and metabolic parameters in Japanese patients with schizophrenia. Methods:We obtained metabolic parameter data from 19,675 patients with schizophrenia. Of these, 1380 (7.0%), 8422 (42.8%), 6326 (32.2%), and 3547 (18.0%) were treated with none, one, two, and three or more antip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The current results replicated the finding in our previous study, which revealed an association between the number of antipsychotics prescribed and BMI in 19,675 patients with schizophrenia. 13 In the current study, 115 of 212 (54.2%) inpatients with schizophrenia received antipsychotic polypharmacy. Notably, 35 (16.5%) inpatients were treated with three or more antipsychotics.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…The current results replicated the finding in our previous study, which revealed an association between the number of antipsychotics prescribed and BMI in 19,675 patients with schizophrenia. 13 In the current study, 115 of 212 (54.2%) inpatients with schizophrenia received antipsychotic polypharmacy. Notably, 35 (16.5%) inpatients were treated with three or more antipsychotics.…”
Section: Discussionmentioning
confidence: 68%
“…In our previous study, 52.3% and 19.5% of 14,234 Japanese inpatients with schizophrenia received antipsychotic polypharmacy and three or more antipsychotics, respectively. 13 Moreover, another recent study reported that 42.9% and 24.1% of 2177 Japanese inpatients with schizophrenia received antipsychotic polypharmacy and three or more antipsychotics, respectively, at discharge. 20 To minimize adverse effects of antipsychotics on BMI, psychiatrists should avoid inappropriate antipsychotic polypharmacy, especially polypharmacy involving three or more antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found, however, a negative correlation between oral atypical antipsychotics and BMI and fasting blood glucose. A study by Watanabe et al . (2022) in Japan reported that the number and type of antipsychotics are significantly associated with diastolic blood pressure and obesity while Aly El-Gabry et al .…”
Section: Discussionmentioning
confidence: 99%